Exciton-polaritons in 2d macroporous silicon structures with nano-coatings - L. A. Karachevtseva; O. O. Lytvynenko; V. F. Onyshchenko; V. V. Strelchuk; V. A. Boyko (Хімія, фізика та технологія поверхні, 2020)
In this paper, we investigated high-resolution IR absorption and reflection spectra in one-sided periodical   2D macroporous silicon structures with nano-coatings of SiO2 and CdS, ZnO nanoparticles, as well as two-sided structures of macroporous silicon without nano-coatings. After changing the resolution of spectra measurements from 2 to 1 cm–1, the oscillation period of Wannier-Stark electro-optical effect decreases by 3 times, and absorption increases by 60–100 times; and for two-sided structures the oscillation period decreases by 1.5 times and absorption increases by 25–30 %. In addition, giant absorption oscillations with positive and negative amplitudes of 107 arb. un. were evaluated in spectral regions of Si–Si–bonds and Pb centers. Similar oscillations in the reflection spectra have much less amplitudes up to 4·104 arb. un. In the spectral area of the transverse phonon ?TO (Si–Si–bonds) absorption spectra of 2D macroporous silicon structures consistent fully with data for phonon polaritons in microresonators as a result of resonance interaction of dipole-active vibrations with the frequency of ?TO in thin films with the surface modes of microresonator. In addition, microresonators interact both with each other in one-sided macroporous silicon structures and in the system of two-sided macroporous silicon. The giant absorption oscillations testify the strong interaction of surface polaritons with photons. The coherence of oscillations and large-scale spatial correlation are а result of exciton-polariton condensation on macropores as microresonators. In 2D macroporous silicon structures with nano-coatings band bending on the surface of the macropores are significant. Therefore, the generated photoelectrons link with holes, forming electron-hole pairs named as exciton-polaritons according to phenomenon of Bose-Einstein condensation.